The Quest to Promote Ideal Early Parenting Philosophy, Skills, and Education - Humenick, Sharron S (Lamaze International, 1999)
Prenates, babies, and children deserve wholesome parents and parenting, now. This is the time in which we are all living and growing. The quest for more optimal parenting will bring about more whole-loving beings. Our children and our planet deserve our best effort. Readers can contribute to coalition building towards that aim.